A falta que me faz Like water through stone / TEIA apresenta ; realização, Marília Rocha ; produção, Luana Melgaço. - H., Arthur 1966- (Ágata Tecnologia Digital Ltda. : Lume Filmes, 2009)
In the Espinhaço Mountains one winter, a group of small-town Brazilian girls are coming to the end of their adolescence. Impossible romances link them with men from the outside, leaving marks on their bodies and the surrounding landscape. Among the parties, friendships, anxieties and contradictions of their passage into adulthood, each of the friends finds her own particular way to resist the changes and to live with the tangle of uncertainty.